2019
DOI: 10.1098/rspb.2019.0331
|View full text |Cite
|
Sign up to set email alerts
|

Haemolymph removal by Varroa mite destabilizes the dynamical interaction between immune effectors and virus in bees, as predicted by Volterra's model

Abstract: The association between the deformed wing virus and the parasitic mite Varroa destructor has been identified as a major cause of worldwide honeybee colony losses. The mite acts as a vector of the viral pathogen and can trigger its replication in infected bees. However, the mechanistic details underlying this tripartite interaction are still poorly defined, and, particularly, the causes of viral proliferation in mite-infested bees. Here, we develop and test a novel hypothesis that mite f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 34 publications
(80 reference statements)
4
77
0
1
Order By: Relevance
“…Both haemocytes and melanin permit the encapsulation of pathogens during infection or wounding, and thus play a role in insect immune response and healing mechanisms [59]. The weakening of honey bee immunity [60,61] may be linked to the finding that mites feed on fat bodies, given that these organs play a major role in immunity [62].…”
Section: What Can It Do?mentioning
confidence: 99%
“…Both haemocytes and melanin permit the encapsulation of pathogens during infection or wounding, and thus play a role in insect immune response and healing mechanisms [59]. The weakening of honey bee immunity [60,61] may be linked to the finding that mites feed on fat bodies, given that these organs play a major role in immunity [62].…”
Section: What Can It Do?mentioning
confidence: 99%
“…However, neonicotinoids are only one of the many stressors impairing honey bee health and survival 5 7 . Among these, a preeminent role is played by the mite Varroa destructor , the most important ectoparasite of honey bees, which is a major problem for honey bee colonies in the Northern hemisphere 8 , 9 ; this is largely related to its activity as a vector and activator of DWV 10 , 11 , with which the mite has established a symbiotic association that exacerbates their respective impacts on honey bee health 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide spread of the Varroa destructor parasite facilitated Deformed wing virus (DWV) infections by acting as an active vector (where the virus can replicate in both the vector and the host) (21). Parallel to its role as viral vector, it has been shown that the V. destructor parasite can also influence the immune status of its host (22). Globalization of V. destructor and concomitant DWV infections raised the question what influence DWV plays in colony health.…”
Section: Introductionmentioning
confidence: 99%